Kerajaan Allah dalam Kisah Para Rasul - Rafiela Loli; Silvia Lola Cantika; Sarmauli Sarmauli (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This research aims to examine the Kingdom of God in the Acts of the Apostles. The research method used in this study is the library research method. This method was chosen because it allows researchers to examine in depth various concepts, theories and empirical findings that have been published by experts relating to the Kingdom of God in the Acts of the Apostles.  From the study that has been described, it can be concluded that the Kingdom of God is God's sovereign government, which is expressed in the person and work of Jesus Christ. The Kingdom of God has a present dimension that can be experienced by believers and a future dimension that will be perfectly fulfilled at the end of time. In the Book of Acts, the Kingdom of God is the main focus of the apostles' preaching. The development of the Kingdom of God occurs through three stages according to the Great Commission: in Jerusalem, in Judea and Samaria, to the ends of the earth. The dynamics of the Kingdom of God are realized through the power of the Holy Spirit, church growth in the midst of persecution, and solving the congregation's internal problems.